Past large earthquakes on the Alpine Fault: paleoseismological progress and future directions. Issue 3 (3rd July 2018) - Howarth, Jamie D.; Cochran, Ursula A.; Langridge, Robert M.; Clark, Kate; Fitzsimons, Sean J.; Berryman, Kelvin; Villamor, Pilar; Strong, Delia T.
ABSTRACT: Paleoseismology has been making an important contribution to understanding the Alpine Fault and the hazard it poses to society. However, evidence of past earthquakes comes from a wide variety of sources and publication of the evidence has been somewhat fragmented. Here, we review physical evidence for past large to great earthquakes on the Alpine Fault to summarise current understanding, illustrate progress and highlight future directions. Paleoseismic evidence has been derived from tree disturbance, landscape features and trenches across the fault. These records have been supplemented and extended back in time with sedimentary evidence of Alpine Fault earthquakes from fault-proximal lakes and wetlands. In this review, we update radiocarbon analyses using recent calibration curves and modern Bayesian statistical methods where necessary to enable comparison between on-fault, fault-proximal and off-fault earthquake records. Over recent decades, Alpine Fault paleoseismology has progressed from playing an important role in demonstrating that large surface-rupturing earthquakes occur, to enabling estimates of earthquake recurrence behaviour, shaking intensities, rupture extents, landscape response durations and likelihood of the next earthquake.